2011
DOI: 10.1159/000335888
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin Level and Copeptin Response to Percutaneous Balloon Mitral Valvuloplasty in Mitral Stenosis

Abstract: We aimed to investigate copeptin levels in mitral stenosis (MS) patients and the behavior of copeptin after hemodynamic improvement achieved by percutaneous balloon mitral valvuloplasty (PBMV). The study involved 29 consecutive symptomatic patients with moderate to severe rheumatic MS who underwent PBMV. Twenty-eight age- and gender-matched healthy volunteers composed the control group. Blood samples for copeptin were obtained immediately before and 24 h after PBMV, centrifuged, then stored at -70°C until assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…In patients with MS, conditions such as decreased preload and stroke volume lead to increase in copeptin levels (9) . In patients with MR, there is a different physiopathology unlike patients with AS and MS and effect on copeptin release seen in this present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with MS, conditions such as decreased preload and stroke volume lead to increase in copeptin levels (9) . In patients with MR, there is a different physiopathology unlike patients with AS and MS and effect on copeptin release seen in this present study.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, copeptin was found a novel biomarker of degenerative AS in patients with preserved LVEF independent of the coexisting coronary artery disease owing to ventricular remodeling and changes in LV volume and LVEF (3) . In another study copeptin was found significantly increased in patients with mitral stenosis (MS) and they also found that after mitral balloon valvuloplasty copeptin levels decreased dramatically (9) . In severe mitral regurgitation (MR), there is a different physiopathology on atrial filling and cardiac output.…”
Section: Introductionmentioning
confidence: 93%
“…[25][26][27][28][29][30] The copeptin concentration in the blood serum was also higher in patients with symptomatic mitral stenosis, which regresses after percutaneous balloon mitral valve plasty, which is observed along with a reduction in the transmitral pressure gradient and systolic pulmonary artery pressure. 31 The importance of copeptin was documented in severe aortic stenosis, with preserved left ventricular systolic function regardless of the copresence of coronary artery disease. 32 The importance of AVP has also been described in cardiovascular shock states.…”
Section: Copeptin In Cardiovascular and Kidney Diseasesmentioning
confidence: 99%
“…The study by Günebakmaz, published in a recent issue of Cardiology [6], comes at a time when biomarkers are gaining importance in cardiopathies regarding diagnosis, prognostication and assessment of the effectiveness of various treatment modalities [2]. The authors used COP in 29 patients undergoing percutaneous mitral balloon valvuloplasty in mitral stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these peptides are an invaluable tool not only for the assessment of the current functional cardiovascular status [10] but also for risk stratification [11]. However, the authors’ data stress the value of biomarkers as surrogate measurement for clinical outcomes [6]. …”
Section: Introductionmentioning
confidence: 99%